synthesis of novel n-Substituted phthalimidyl esters and thier applications (Baghdad Science Journal, 2006)
Research has included preparation of three of n Vthal acids Amec Bmentoj high of interaction vehicles Ortometta and bar aminophenol with phthalic anhydride was withdrawn water and ring closure of acids Alvthal AMEC prepared